Safety and effectiveness of the combination of remimazolam tosilate and propofol in gastroscopy: a multicenter, randomized controlled, single-blind clinical trial - Wang, Chunyan; Gao, Yangzheng; Li, Jie; Zhang, Linlin; Li, Qing; Li, Yize; Lu, Yuechun; Sun, Jiangang; Zhang, Yang; Cheng, Yaobei; Zhang, Shidong; Wang, Guolin; et al. (Frontiers in Pharmacology, 2023)
Remimazolam tosilate (RT) is a new short-acting γ-aminobutyric acid A (GABAA) receptors agonist. However, its optimal use mode and dosage still remain unclear. This study aimed to examine the safety and effectiveness of the combination of RT and propofol in gastroscopy. This was a prospective, single-blind, randomized, multicenter, parallel-group study. All eligible 256 patients were randomized into the following 3 groups. Patients were anesthetized with propofol (Group P), RT (Group R) or the combination of RT and propofol (Group RP). The primary efficacy endpoints were: body movement score; satisfaction of gastroscopy doctors; success rate of sedation and effects on sleep status. Sedation induction time, time to be fully alert and adverse events were also recorded. The probability of complete immobility was lower in group R (33.73%) than in group P (86.67%) and RP (83.13%). The rate of doctors’ satisfaction was much lower in group R (28.92%) than in group P (77.78%) and RP (72.29%). The success rate of sedation and sleep outcome score has no difference in the three groups. The time to adequate sedation was longer in group RP (77.27 ± 18.63 s) than in group P (64.47 ± 24.36 s), but much shorter than that in group R (102.84 ± 46.43s). The time to be fully alert was shorter in group R (6.30 ± 1.52 min) and RP (6.54 ± 1.13 min) than in group P (7.87 ± 1.08 min). The proportion of sedative hypotension was significantly higher in group P (41.11%) than in group R (1.20%) and group RP (3.61%) (p < 0.001). The incidence of respiratory depression was much higher in group P (17.78%) than in group R (no patient) and group RP (1.2%). The incidence of adverse events was lower in groups R (4.82%) and RP (9.64%) than in group P (31.11%). The combination of RT and propofol takes effect quickly, makes patients alert quickly, provides a sufficient depth of sedation, reduces body movement, does not inhibit circulation and respiratory function, does not affect sleep, and is the preferred mode for gastroscopy doctors and anesthesiologists.